Resource at risk Philippine marshlands. - Regalado, Nonoy; Alcantara, An Mercado; Tan, Jose Ma. Lorenzo (Bookmark, 2000)
A video on the Agusan Marsh, the country's largest remaining freshwater wetland. It also shows how the Agusan Manobo have adapted to the harsh conditions of the marsh. Ecologists working for the preservation of the marsh's wildlife and forestry are featured. This documentary educates viewers on the importance of the marshlands in maintaining the ecological balance in Agusan.